Life time and mobility product of injected charge carriers in copper II phthalocyanine thin films with different phase structure - Lkhamsuren, Enkhtur; Ragchaa, Galbadrakh; Шилагарди, Г. (Scientific transaction of the National University of Mongolia. Physics, 2022)
Using near-field scanning microwave microprobe (NSMM) method we have observed the distribution of injected charge carriers along conductivity channel in CuPc thin film on dependence of applied bias. From scan data were calculated diffusion length and product fi-r for injected charges from Au electrode to CuPc thin film. By scanning electron microscopy method were investigated morphology properties of CuPc thin films, which explains the difference of product /n-r for injected charge carriers in CuPc thin films with different crystal phase structure.